PENGARUH MODEL MULTILITERASI TERHADAP KEMAMPUAN MENULIS PIDATO PADA SISWA KELAS XI SMAS HARAPAN MEDAN - Salsabila Miska Puteri; Siti Fatimah Zahara; Sri Muliatik (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aims to determine the effect of the implementation of the multiliteracy learning model on the ability to write speech texts of class XI students of SMAS Harapan Medan. This study was motivated by the low ability of students in writing structured, communicative, and persuasive speech texts. The research method used was a quasi-experiment with a one-group pretest–posttest design. The study population was all class XI students of SMAS Harapan Medan in the 2025–2026 academic year, and the sample was determined using a saturated sampling technique. The research instrument was a speech text writing test given before and after the implementation of the multiliteracy learning model. Data were analyzed using a paired sample t-test. The results showed that there was a significant increase in students' speech text writing abilities after the implementation of the multiliteracy learning model, with a significance value of p <0.05. This finding proves that the multiliteracy learning model has a positive and significant effect on students' speech text writing abilities. Thus, the multiliteracy learning model is effective for use in speech writing learning at the high school level.